Role of precession on the transition seasons of the Asian monsoon - Chi-Hua Wu; Shih-Yu Lee; John C. H. Chiang; Pei-Chia Tsai (npj Climate and Atmospheric Science, 2023)
Abstract While there have been many paleoclimate studies on the precessional control of climate, typically only the orbital phase where perihelion occurs close to the solstices has received attention. Here, we explore how precession affects the seasonal evolution of the Asian summer monsoon in the transitional seasons of boreal spring and autumn. With perihelion occurring in boreal spring, the Hadley circulation weakens over the northern Indian Ocean, linked to precession-enhanced sensible heating over the Tibetan Plateau. There is an early northward migration of the midlatitude westerly jet stream, and the advancement of the pre-monsoon along the Asian–Australian land bridge. The pre-monsoon response to precession may have had a major role in the early part of the last deglaciation, when perihelion last occurred during boreal spring. A weak continental summer monsoon and autumn aphelion during the early part of the last deglaciation led to a weak Pacific high over the east of coastal East Asia, allowing for a vigorous oceanic western North Pacific monsoon in the late summer. Additionally, the seasonal expansion of oceanic monsoon trough could shed light on the quasi-stationarity of the oceanic monsoon during a precessional cycle.